Synthesis and characterization of high photo luminescence of CPC capped bis (8-hydroxyquinoline) zinc nano rods. (2020) - Bharathi Devi, V.; Andal, C.; Arulmozhichelvan, P.; Murugakoothan, P.
Abstract: Highly luminescent bis (8-hydroxyquinoline) zinc nanorods with average thickness of 76 nm and length up to a few micrometers have been synthesized via simple precipitation method using Cetyl pyridinium chloride (CPC) as a surfactant. The synthesized Znq2 was annealed at 200 °C in air for 3 h. The obtained nano rods were studied by powder X-ray diffraction (PXRD) to confirm the crystalline nature of the particles. The thermal property of the particles were studied using TG-DTA analysis. The morphology and presence of elements were studied by High Resolution scanning electron microscopy (HRSEM) and Energy dispersive analysis of X-rays (EDAX). The functional groups of the particles were confirmed by FTIR spectroscopy. The optical properties of the particles were studied by UV–visible spectroscopy and photoluminescence spectroscopy. The band gap of the particles was calculated. The synthesized CPC capped Znq2 nano particles were confirmed by photoluminescence studies for OLED applications as emission and electron transport layers.